Electric and magnetic axion quark nuggets, their stability and their detection - Santillán, Osvaldo Pablo (2020)
The present work studies the dynamics of axion quark nuggets introduced in Zhitnitsky (JCAP 0310:010, 2003) and developed further in the works (Zhitnitsky in Phys Rev D 74:043515, 2006; Lawson and Zhitnitsky in Phys Lett B 724, 17, 2013; Lawson and Zhitnitsky in Phys Rev D 95:063521, 2017; Liang and Zhitnitsky in Phys Rev D 94:083502, 2016; Ge et al. in Phys Rev D 97:043008, 2018; Zhitnitsky in Phys Dark Univ 22:1, 2018; Lawson and Zhitnitsky in Phys Dark Univ 100295, 2019; Raza et al. in Phys Rev D 98:103527, 2018; Fischer et al. in Phys Rev D 98:043013, 2018; van Waerbeke and Zhitnitsky in Phys Rev D 99:043535, 2019; Flambaum and Zhitnitsky in Phys Rev D 99:043535, 2019; Lawson and Zhitnitsky in JCAP 02:049, 2017; Ge et al. in Phys Rev D 99:116017, 2019). The new feature considered here is the possibility that these nuggets become ferromagnetic. This possibility was pointed out in Tatsumi (Phys Lett B 489:280 2000) for ordinary quark nuggets, although ferromagnetism may also take place due some anomaly terms found in Son and Zhitnitsky (Phys Rev D 70:074018, 2004), Son and Stephanov (Phys Rev D 77:014021, 2008) and Melitski and Zhitnitsky (Phys Rev D 72:045011, 2005). The purpose of the present letter however, is not to give evidence in favor or against these statements. Instead, it is focused in some direct consequences of this ferromagnetic behavior, if it exists. The first is that the nugget magnetic field induces an electric field due to the axion wall, which may induce pair production by Schwinger effect. Depending on the value of the magnetic field, the pair production can be quite large. A critical value for such magnetic field at the surface of the nugget is obtained, and it is argued that the value of the magnetic field of Tatsumi (2000) is at the verge of stability and may induce large pair production. The consequences of this enhanced pair production may be unclear. It may indicate that the the nugget evaporates, but on the other hand it may be just an indication that the intrinsic magnetic field disappears and the nuggets evolves to a non magnetized state such as in Zhitnitsky (2003), Oaknin and Zhitnitsky (Phys. Rev. D 71:023519, 2005), Zhitnitsky (2006), Lawson and Zhitnitsky (2013), Lawson and Zhitnitsky (2017), Liang and Zhitnitsky (2016), Ge et al. (2018), Zhitnitsky (2018), Lawson and Zhitnitsky (2019), Raza et al. (2018), Fischer et al. (2018), van Waerbeke and Zhitnitsky (2019), Flambaum and Zhitnitsky (2019), Lawson and Zhitnitsky (2017), and Ge et al. (2019). The interaction of such magnetic and electric nugget with the troposphere of the earth is also analyzed. It is suggested that the cross section with the troposphere is enhanced in comparison with a non magnetic nugget but still, it does not violate the dark matter collision bounds. Consequently, these nuggets may be detected by impacts on water or by holes in the mountain craters (Pace VanDevender et al. in Sci Rep 7:8758, 2017). However, if the magnetic field does not decay before the actual universe, then this would lead to high energy electron flux due to its interaction with the electron gases of the Milky Way. This suggests that these magnetized quarks may be a considerably part of dark matter, but only if their hypothetical magnetic and electric fields are evaporated.